2015
DOI: 10.5615/neareastarch.78.3.0142
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Imagery-Based Analysis of Archaeological Looting in Syria

Abstract: The Bronze Age site of Mari on the Euphrates River in eastern Syria appearing in a satellite image from April 11, 2015. The upper mound of the site, surrounding the excavated palace of Zimri-Lim, has been severely looted in recent years. Imagery © Digital Globe 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 9 publications
0
69
1
2
Order By: Relevance
“…Our major conclusions-that looting is a regionally-specific phenomenon in Afghanistan carried out by multiple actors (not just the Taliban) and that other forms of development-related DRAFT OF PUBLISHED ARTICLE: PLEASE CITE ONLY PUBLISHED VERSION destruction (related to agriculture, urban expansion, and mining) are individually and collectively more pressing threats to archaeological sites than looting-are paralleled by those of collaborative projects studying the fate of cultural heritage in the post-Arab-Spring Middle East. For example, spatial analysis of recent looting patterns at over almost 3000 sites in Syria showed that looting is carried out in territory controlled by various factions involved in the Syrian Civil War, not just extremists like the Islamic State, whose performative destructions have been the focus of international media reports [2,28]. Further, this systematic study found that agricultural and urban expansion were the most prevalent forms of damage to heritage sites in war-torn Syria, not looting or military damage.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Our major conclusions-that looting is a regionally-specific phenomenon in Afghanistan carried out by multiple actors (not just the Taliban) and that other forms of development-related DRAFT OF PUBLISHED ARTICLE: PLEASE CITE ONLY PUBLISHED VERSION destruction (related to agriculture, urban expansion, and mining) are individually and collectively more pressing threats to archaeological sites than looting-are paralleled by those of collaborative projects studying the fate of cultural heritage in the post-Arab-Spring Middle East. For example, spatial analysis of recent looting patterns at over almost 3000 sites in Syria showed that looting is carried out in territory controlled by various factions involved in the Syrian Civil War, not just extremists like the Islamic State, whose performative destructions have been the focus of international media reports [2,28]. Further, this systematic study found that agricultural and urban expansion were the most prevalent forms of damage to heritage sites in war-torn Syria, not looting or military damage.…”
Section: Discussionmentioning
confidence: 82%
“…To date, we have examined only sites from the 1982 Gazetteer, which are likely to be among the largest sites in Afghanistan. Different phases of systematic damage assessment across Syria, Iraq, southern Turkey, and Lebanon show that heritage conclusions shift based on whether assessments include only large, important "priority" sites [2,29] or whether they include sites mapped only via satellite imagery that have previously been unknown to researchers [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations